From hygienism to taylorism: how the projects became the urban reality of medellín in 1870-1932 (2007)
The growth the city of Medellín in Colombia, has been explained by historians and researchers from the perspective of two urban projects: the first one, which was made of the colonial Indian dammar, and the second one –Haussmann’s project, coming from the second version of Plans of the Future Medellín City in the begining of the XX century. However, both projects are just myths and simplifications, similar to those studied of other cities in Latin America. Even if some aspects of the Haussmann’s project had been raised, as the beauty or the aesthetics, the hygiene and the interest of commerce, those also came from other sources and from some smaller projects presented by Haussmann. During the years betwen 1870 to 1932 there were plenty of plans developed from the French and English hygienist movement, from Cerdá’s scientific urbanism in Barcelona, the technical pragmatism presented by Baumeister in Germany, from English and American issues of City Planning Town Planning and Howard’s Garden City and Garden Suburb, Unwin y Griffin, and even Henry Prost’s Plan Directeur of Paris, and the urban art of Camilo Sitte. This essay recognizes different contributions and project ideas transfered from Europe and America into Medellín, their transformations and adaptationes, also ideas not directly related to urbanism, as Taylor’s economy for instance. The economical taylorism had been adapted to impulse the development of the city and to create the modern urban culture during the period.